Investigating a socially anxious‐impulsive subgroup of adolescents: A prospective community study. Issue 3 (4th March 2013) - Tillfors, Maria; Van, Nejra; Kerr, Margaret
<x xml:space="preserve">Abstract</x> Previous research has identified a subgroup of socially anxious adults who are both anxious and impulsive. To date, however, this subgroup has not been identified in adolescence. Therefore, in this study we aimed to identify this subgroup in a sample of adolescents. In addition, we hypothesized that this subgroup would be higher on problem behaviors, and that these processes would be moderated by gender. We used longitudinal data from 714 adolescents who were in the 7th and 8th grades at Time 1. They were followed annually for three years. Cluster analyses identified an anxious‐inhibited subgroup as well as an anxious‐impulsive subgroup in early adolescence (Time 1). The socially anxious‐impulsive adolescent boys were generally higher on both intoxication frequency and delinquency compared with all other adolescents in all clusters at each time point. Findings suggest that social anxiety subgroups may differ on problem behavior, and that early detection of an anxious‐impulsive subgroup may be important to prevent maladjustment, especially for adolescent boys.